PERCEPTION ON BASIC BANKING SERVICES – A STUDY - A, Suresh; Narayana, M. Srinivasa; Kumar, P. Vijay (International Journal of Psychosocial Rehabilitation, 2020)
The government and all the important stakeholders of the country are aiming to bring all the rural poor into the banking fold to uplift the economic condition of these people. As part of this the process, Financial Inclusion is initiated where access to appropriate financial products and services are offered at an affordable price which allows to manage their financial resources effectively irrespective of their level of income or social status. The Indian economy and the banking services made rapid strides over the years and observed the need for an indispensable participation of all sections of society. To have an inclusive growth the weaker sections and low income groups should have a savings bank account or avail a loan from a formal financial institution. There are various steps taken by the government in promoting financial inclusion such as relaxation of KYC norms, feasibility in opening bank accounts, providing insurance and pension schemes etc. for upliftment of the economic conditions of the rural poor. In the present paper, five mandals from Guntur district are considered and a survey is conducted to analyze the type of accounts, reasons for having the accounts, frequency of visiting the bank and the purpose of visiting the bank etc. were discussed to ascertain the level of utilization of the basic banking operations among the respondents.